China's involvement in the trans-Saharan textile trade and industry in Nigeria: the case of Kano. Issue 163 (2nd January 2020) - Muhammad, Murtala; Buba, Ramatu; Azman, Muhammad Danial; Ahmed, Abubakar
SUMMARY: This Briefing analyses the large volume and value of smuggled Chinese textile products through the Sahara into the Kano market from 2000 to 2015. The evidence indicates that China's involvement has displaced local manufacturers in the historic textile city of Kano.